Exploring Business Potential Through the Application of Artificial Intelligence: Impact Analysis on Operational Efficiency, Decision Making, and Customer Experience - Setia Putra, Hari; Badri, Juarsa; Irfani, Hadi (Escalate : Economics and Business Journal, 2024)
This article investigates the transformative impact of Artificial Intelligence (AI) on business dynamics through multiple linear regression analysis. Using data from PT. Samudera Indonesia Padang Branch, this research evaluates the influence of operational efficiency with the application of AI (X1), decision making supported by AI technology (X2), and efforts to improve customer experience through AI innovation (X3) on the Evaluation of the Impact of AI-Based Marketing Strategy variables (dependent) . The results show a robust model, with an R-square value of 0.783, indicating that approximately 78.3% of the variability in the dependent variable is explained by the AI-driven predictor variables. Each variable demonstrated a positive and substantial impact, emphasizing the importance of AI in improving operational processes, decision making and customer interactions. The high F-square value of 47.342 confirms the statistical significance of the entire model. This study contributes to understanding how AI adoption in business drives innovation and success, providing valuable insights for organizations looking to harness the potential of AI in a rapidly evolving business landscape.